A peptide‐display protein scaffold to facilitate single molecule force studies of aggregation‐prone peptides. (10th March 2018) - Doherty, Ciaran P. A.; Young, Lydia M.; Karamanos, Theodoros K.; Smith, Hugh I.; Jackson, Matthew P.; Radford, Sheena E.; Brockwell, David J.
Abstract: Protein aggregation is linked with the onset of several neurodegenerative disorders, including Parkinson's disease (PD), which is associated with the aggregation of α‐synuclein (αSyn). The structural mechanistic details of protein aggregation, including the nature of the earliest protein–protein interactions, remain elusive. In this study, we have used single molecule force spectroscopy (SMFS) to probe the first dimerization events of the central aggregation‐prone region of αSyn (residues 71–82) that may initiate aggregation. This region has been shown to be necessary for the aggregation of full length αSyn and is capable of forming amyloid fibrils in isolation. We demonstrate that the interaction of αSyn71‐82 peptides can be studied using SMFS when inserted into a loop of protein L, a mechanically strong and soluble scaffold protein that acts as a display system for SMFS studies. The corresponding fragment of the homolog protein γ‐synuclein (γSyn), which has a lower aggregation propensity, has also been studied here. The results from SMFS, together with native mass spectrometry and aggregation assays, demonstrate that the dimerization propensity of γSyn71‐82 is lower than that of αSyn71‐82, but that a mixed αSyn71‐82 : γSyn71‐82 dimer forms with a similar propensity to the αSyn71‐82 homodimer, slowing amyloid formation. This work demonstrates the utility of a novel display method for SMFS studies of aggregation‐prone peptides, which would otherwise be difficult to study.